Penerapan Pembelajaran SETS (Science, Environment, Technology and Society) untuk meningkatkan Pemahaman Kebencanaan Tsunami Peserta didik pada materi Gelombang Mekanik (IPF: Inovasi Pendidikan Fisika, 2022)
Seeing the high potential that Indonesia has in dealing with the tsunami, an effort is needed to understand and prepare in order to anticipate and reduce the impact of the disaster. To understand a disaster, it is necessary to study the concepts and basics related to disaster which includes the physical process that can be caused by the disaster. The aims of this research are (1) to analyze the implementation of Science, Environment, Technology and Society learning to improve understanding of disaster and (2) to analyze the learning outcomes of Science, Environment, Technology and Society towards disaster understanding. This type of research is quantitative research using experimental research methods. This study used a one-group design, namely a one-group pretest-posttest design. This research was conducted at SMA Kartika Wijaya in class XI MIPA with 35 students. The results show that the teacher can implent SETS model learning well for the two observers, which is 71.87% to 76.56% for the first observer and 85.90% to 87.50% for the second observer. SETS Model learning on mechanical wave material can improve understanding of disaster. This is evidenced by the N-gain value obtained at 0.73 which is categorized as high. The findings of this study can be used as a starting point for research to examine the SETS Model learning by taking into account the positive impact of learning. Suggestions for future researchers are to use other learning models to improve understanding of disasters and to use examples of natural disasters other than tsunamis Keywords: SETS Model Learning, Understanding Disaster, Tsunami, Mechanical Waves